A highly conserved repetitive DNA sequence, (TTAGGG)n, present at the telomeres of human chromosomes. - Moyzis, R K (1988)
A highly conserved repetitive DNA sequence, (TTAGGG)n, has been isolated from a human recombinant repetitive DNA library. Quantitative hybridization to chromosomes sorted by flow cytometry indicates that comparable amounts of this sequence are present on each human chromosome. Both fluorescent in situ hybridization and BAL-31 nuclease digestion experiments reveal major clusters of this sequence at the telomeres of all human chromosomes. The evolutionary conservation of this DNA sequence, its terminal chromosomal location in a variety of higher eukaryotes (regardless of chromosome number or chromosome length), and its similarity to functional telomeres isolated from lower eukaryotes suggest that this sequence is a functional human telomere.